Pengembangan Media DIA-VAR (Diorama Variasi Augmented Reality) Menggunakan Assemblr Edu pada Kelas IV Sekolah Dasar - Indah Khoirunnisa; Desy Rosmalinda; Ifna Mutia (STKIP Subang, 2025)
This study aims to develop and determine the potential feasibility of the DIA-VAR (Diorama Variation Augmented Reality) learning media using the Assemblr Edu platform for the subject matter of Diverse Landforms and their relation to Professions in Grade IV of Elementary School. The necessity of this media emerged from an analysis identifying low student engagement and the limited use of interactive digital technology in visualizing abstract IPAS (Science and Social Studies) concepts. The development process follows the systematic ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The final product is designed to combine a physical diorama with interactive Augmented Reality (AR) features. This study’s primary objective is to produce a media that is theoretically valid, highly practical, and provides an effective, contextual solution to enhance students' comprehension and motivation toward IPAS material